Health services teams’ competences in mental health: the NEAD-UFES case - Siqueira, Marluce Miguel de (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2009)
Social changes have influenced in different ways the existence of the human kind, especially in education and labor. These changes have indicated the need to reformulate both the process of training and the wok of health professionals. Thus, this critical reflexive study approaches competences used in the mental health area, based on authors' experiences in the nursing team of the Study Group on Alcohol and other Drugs (NEAD) of the Federal University of Espirito Santo (UFES). The article shows that the creation of a space to study the teaching and practice on psychoactive substances directed to Nursing and other students from UFES, made possible to build a concept about competences in mental health in a critical, participative and conscious way.